Persepsi Mahasiswa Bercadar IAIN Padangsidimpuan terhadap Proses Pemilihan Presiden Tahun 2019 - Marpaung, Lidya Nurjannah; Siregar, Khoiruddin Manahan (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2023)
This study discusses the Political Participation of Veiled Students of the Padangsidimpuan State Islamic Institute in the 2019 Presidential Election in the City of Padangsidimpuan. The type of research is field research (field research) with a field approach. The date source consisted of primary, nmaelyveiled studets at IAIN Padangsidimpuan and secondary books, journal article, documentation, relevant to this study. Date collection techniques are obsevation, interviws, and analysis techniques are descriptive analysis.. This secondary data consists of literature which is reading material, the work of experts from their respective fields whose function is to explain primary legal materials. After obtaining complete data, it is then analyzed to get more relevant results. The results of the study stated that the Political Participation of Veiled Padangsidimpuan State Islamic Institute Students in the 2019 Presidential Election in Padangsidimpuan City was still very minimal as can be seen from the level of participation of Padangsidimpuan State Islamic Institute students who wore veils in the presidential election in Padangsidimpuan city where there were 32% who voted. and did not vote 68%. The results of the study show that the factors that affect the low level of political participation of female students are first, educational background, second, environment, and third, the many political actors who deviate. The consequences are first, the bad democratic system and second, the decline in the level of public trust in the government.